2017
DOI: 10.5482/hamo-16-06-0017
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of immune thrombocytopenia in childhood

Abstract: Evidence-based medicine is growing in immune thrombocytopenia (ITP), but solid clinical data are still lacking in many areas. A majority of children has self-limited ITP, but chronic symptomatic ITP exists also in pediatrics. Management includes a watch-and-wait strategy for children with newly diagnosed ITP and no or mild bleeding, and immunoglobulins and corticosteroids, if more bleeding and mucous membrane involvement is present. Treatment endpoints differ in clinical research and in clinical practice. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 89 publications
1
22
0
3
Order By: Relevance
“…Many retrospective and prospective studies also confirmed a similar or higher efficacy of splenectomy in children with chronic ITP. For example, data from 153 children with a median follow‐up of 2 years showed immediate platelet response in 86% with 80% maintaining their response in the following 4 years (Kuhne et al , ; Kuhne, ).…”
Section: Consolidated Results Of Splenectomymentioning
confidence: 99%
“…Many retrospective and prospective studies also confirmed a similar or higher efficacy of splenectomy in children with chronic ITP. For example, data from 153 children with a median follow‐up of 2 years showed immediate platelet response in 86% with 80% maintaining their response in the following 4 years (Kuhne et al , ; Kuhne, ).…”
Section: Consolidated Results Of Splenectomymentioning
confidence: 99%
“…The standard first-line therapy for ITP consist in corticosteroids and intravenous immunoglobulins (IVIG). 2,3 Childhood ITP is a heterogeneous disease, which can coexist with several autoimmune diseases, 3 especially in the chronic forms associated with systemic lupus erythematosus (SLE), autoimmune thyroiditis, and hemolytic anemia. 4,5 The combination of immune thrombocytopenia with thyroid autoimmune diseases is an infrequent but well-known condition.…”
Section: Hematology // Endocrinologymentioning
confidence: 99%
“…Dexamethason wurde erstmals in den 1990er Jahren in der Zweitlinientherapie der therapierefraktären, chronischen ITP eingesetzt [68] [5,74,75].…”
Section: Prednison Versus Dexamethasonunclassified